Narrative expressivism: a criminological approach to the expressive function of international criminal justice - Bringedal Houge, Anette (Criminology & criminal justice, 2019)
In response to recent demands to make use of international criminal justice institutions’ archives for social scientific research, this article develops a theoretical approach to international criminal justice called narrative expressivism. Narrative expressivism considers criminal justice as a potent source of information about past crimes - yet also, as a site that impacts on present and future societal understandings of mass violence, promoting a particular structuring of thought. As such, narrative expressivism addresses what kind of knowledge international criminal justice, its institutions and archives, provide the empirical basis for. Theorizing expressivism through a narrative lens, narrative expressivism shifts the emphasis of legal expressivist approaches from facts to stories, from punishment to process, from purpose to function, and from the normative to the descriptive.